Analysis of Variation in the Number of Layers in the Hardfacing Process of ASTM A216 WCB Material on Hardness, Wear, and Microstructure - Wibowo, Alvalo Toto; Al Amin, Mochammad Karim; Wahyudi, Mohammad Thoriq; Kurniyanto, Hendri Budi; Amri, Moh. Syaiful; Firmansyah, Moch. Aria; Leonard, Rikky; Wijaya, Alvido Toto (PENA TEKNIK: Jurnal Ilmiah Ilmu-Ilmu Teknik, 2025)
The selection of transportation fleets plays a crucial role in determining the cost efficiency of logistics operations. This study aims to evaluate the feasibility of investing in company-owned vehicles compared to using third-party rental services on the Bandung–KTSH route operated by PT X. Using a quantitative approach with a causal associative design, this research applies the Vehicle Operating Cost (VOC) method supported by investment feasibility analysis tools including Cash Flow, Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PBP). The analysis shows that the average daily operational cost of company-owned vehicles reaches IDR 1.904.479, which is higher than the rental cost of IDR 1.865.385 per day. Additionally, the results show a negative NPV (-IDR 344.739.419), negative IRR (–11%), and an unattainable payback period within the 5-year investment horizon. Therefore, it is concluded that using leased vehicles is more cost-efficient than investing in company-owned trucks for this specific route.